Three dimensional reconstruction by electron microscopy in the life sciences: An introduction for cell and tissue biologists. Issue 7 (4th February 2015) - Miranda, Kildare; Girard‐Dias, Wendell; Attias, Marcia; de Souza, Wanderley; Ramos, Isabela
SUMMARY: Early applications of transmission electron microscopy (TEM) in the life sciences have contributed tremendously to our current understanding at the subcellular level. Initially limited to two‐dimensional representations of three‐dimensional (3D) objects, this approach has revolutionized the fields of cellular and structural biology–being instrumental for determining the fine morpho‐functional characterization of most cellular structures. Electron microscopy has progressively evolved towards the development of tools that allow for the 3D characterization of different structures. This was done with the aid of a wide variety of techniques, which have become increasingly diverse and highly sophisticated. We start this review by examining the principles of 3D reconstruction of cells and tissues using classical approaches in TEM, and follow with a discussion of the modern approaches utilizing TEM as well as on new scanning electron microscopy‐based techniques. 3D reconstruction techniques from serial sections and (cryo) electron‐tomography are examined, and the recent applications of focused ion beam‐scanning microscopes and serial‐block‐face techniques for the 3D reconstruction of large volumes are discussed. Alternative low‐cost techniques and more accessible approaches using basic transmission or field emission scanning electron microscopes are also examined. Mol. Reprod. Dev. 82: 530–547, 2015. © 2015 Wiley Periodicals, Inc .